Myeloid malignancies with translocation t(4;12)(q11‐13;p13): molecular landscape, clonal hierarchy and clinical outcomes. Issue 20 (7th September 2021) - Parinet, Vincent; Chapiro, Elise; Bidet, Audrey; Gaillard, Baptiste; Maarek, Odile; Simon, Laurence; Lefebvre, Christine; Defasque, Sabine; Mozziconacci, Marie‐Joelle; Quinquenel, Anne; Decamp, Matthieu; Lifermann, François; et al.
Abstract: Translocation t(4;12)(q11‐13;p13) is a recurrent but very rare chromosomal aberration in acute myeloid leukaemia (AML) resulting in the non‐constant expression of a CHIC2 / ETV6 fusion transcript. We report clinico‐biological features, molecular characteristics and outcomes of 21 cases of t(4;12) including 19 AML and two myelodysplastic syndromes (MDS). Median age at the time of t(4;12) was 78 years (range, 56–88). Multilineage dysplasia was described in 10 of 19 (53%) AML cases and CD7 and/or CD56 expression in 90%. FISH analyses identified ETV6 and CHIC2 region rearrangements in respectively 18 of 18 and 15 of 17 studied cases. The t(4;12) was the sole cytogenetic abnormality in 48% of cases. The most frequent associated mutated genes were ASXL1 (n = 8/16, 50%), IDH1 / 2 (n = 7/16, 44%), SRSF2 (n = 5/16, 31%) and RUNX1 (n = 4/16, 25%). Interestingly, concurrent FISH and molecular analyses showed that t(4;12) can be, but not always, a founding oncogenic event. Median OS was 7.8 months for the entire cohort. In the 16 of 21 patients (76%) who received antitumoral treatment, overall response and first complete remission rates were 37% and 31%, respectively. Median progression‐free survival in responders was 13.7 months. Finally, t(4;12) cases harboured many characteristics of AML with myelodysplasia‐related changes (multilineage dysplasia, MDS‐related cytogenetic abnormalities, frequent ASXL1 mutations) and a poor prognosis.